2008
DOI: 10.1159/000119739
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Outcome in Psychotherapy

Abstract: Background: About 25% of all patients seeking psychotherapeutic treatment are considered to be alexithymic. Alexithymia has been assumed to be negatively associated with therapeutic outcome. On the other hand, it is unclear to which extent alexithymia itself may be modified by psychotherapeutic interventions. Methods: From 414 consecutively admitted inpatients, 297 were followed up after 4 weeks (t1) and after 8–12 weeks (t2) upon discharge. Patients were treated with psychodynamic group therapy in a naturalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
87
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 72 publications
(46 reference statements)
8
87
0
12
Order By: Relevance
“…[10][11][12] Studies on this issue suggested that alexithymic features may negatively affect the long-term alcoholism treatment outcomes and that they may also predict alcohol use. 13,14 In recent years, several researchers have emphasized the need for linking personality constructs with neurobiological processes that might underlie individual differences in personality. 15 Some studies have explored the relationship between alexithymia and personality traits measured with the Neuroticism, Extraversion/Introversion, and Openness to Experience-Personality Inventory (NEO-PI), which is a measure of the five major domains of personality as well as the six facets that define each domain.…”
mentioning
confidence: 99%
“…[10][11][12] Studies on this issue suggested that alexithymic features may negatively affect the long-term alcoholism treatment outcomes and that they may also predict alcohol use. 13,14 In recent years, several researchers have emphasized the need for linking personality constructs with neurobiological processes that might underlie individual differences in personality. 15 Some studies have explored the relationship between alexithymia and personality traits measured with the Neuroticism, Extraversion/Introversion, and Openness to Experience-Personality Inventory (NEO-PI), which is a measure of the five major domains of personality as well as the six facets that define each domain.…”
mentioning
confidence: 99%
“…[18] Bu görüşle de paralel olarak, aleksitimik özellikle-rin, kesin sabitlikte olmadığı ve psikoterapi ile değişebilir olduğunu ileri süren araştır-malar yapılmış ve aleksitiminin tedavisi konusundaki tartışmaların sürmesine yol açmış-tır. [9] Bu süreçte aşılması gereken engellerin saptanmasının, çözüm üretmenin ilk basamağı olduğunu düşünüyoruz. Bu sebeple bu noktada aleksitimik bireylerin psikoterapide bağlanma ve ilerleme sorununu detaylı bir biçimde ele almanın faydalı olacağı kanaatindeyiz.…”
Section: Farmakoterapiden Psikoterapiyeunclassified
“…[8] Bununla paralel olarak, güncel klinik gözlemler ve kontrol çalışmaları, aleksitimik hastalarla psikoterapötik tedavinin zorluğuna işaret etmekte ve aleksitimi düzeyi arttıkça terapi sonucunun kötüleştiğini ortaya koymaktadırlar. [8,9] Grabe ve arkadaşlarının özetlediği üzere, bazı etkenlerin psikoterapiye verilen yanıtı olumsuz etkilediği düşünülmektedir. İlk olarak, aleksitimik bireylerin genellikle sosyal olarak kaçıngan, soğuk, diğerlerine duygusal olarak daha az bağlı oldukları varsayılmak-ta, bunun da psikoterapiye cevap verme oranını düşürdüğü ileri sürülmektedir.…”
Section: Psikoterapide Bağlanma Ve İlerleme Sorunuunclassified
See 2 more Smart Citations